Efficacy of Bevacizumab Combined with Pemetrexed in the Treatment of Recurrent and Metastatic Cervical Cancer - He, Ying; Wang, Jing; Xie, Shuangshuang; Xue, Qianlong (Frontiers in Surgery, 2022)
Background: To investigate the efficacy and safety of bevacizumab combined with pemetrexed in the treatment of recurrent and metastatic cervical cancer. Methods: Clinical data of 65 patients with recurrent and metastatic cervical cancer who were admitted to our hospital were collected for retrospective analysis. All patients were administered with bevacizumab combined with pemetrexed for 4-6 cycles (21 days as 1 cycle). The short-term clinical efficacy and adverse reactions were compared between the two groups. In addition, the survival status of patients was followed up and recorded. Results: At least 4 cycles of chemotherapy were given to the 65 patients. There were 0 cases of CR, 14 cases of PR, 36 cases of SD and 15 cases of PD. The objective response rate (ORR) and the disease control rate (DCR) were 21.5% (14/65) and 76.9% (50/65), respectively. DCR was superior in patients with squamous cell carcinoma to that in those with adenocarcinoma (P=0.039), but no statistically significant difference was found in ORR. Patients with extra-pelvic metastatic lesions had a better efficacy than those with intra-pelvic metastatic lesions, but the difference was not statistically significant (P>0.05). The post-treatment adverse reactions mainly involved fatigue, nausea and vomiting, bleeding, leukopenia, anemia, thrombocytopenia, transaminase elevation, hypertension, proteinuria and neurotoxicity, most of which were grade I-II that ameliorated after symptomatic therapy. Grade III adverse reactions mainly included pain in 5 cases (7.7%), leukopenia in 17 cases (26.2%), anemia in 22 cases (33.8%), thrombocytopenia in 6 cases (9.2%), hypertension in 5 cases (7.7%) and neurotoxicity in 7 cases (10.8%). The follow-up results manifested that median overall survival (OS) and median progression-free survival (PFS) were 10.6 months and 6.6 months, respectively. Conclusion: Bevacizumab combined with pemetrexed exhibits certain efficacy in the treatment of recurrent and metastatic cervical cancer, with tolerable adverse reactions. Therefore, this therapeutic option deserves clinical popularization and application.